Comparative power law analysis of structured breast phantom and patient images in digital mammography and breast tomosynthesis. Issue 8 (26th July 2013) - Cockmartin, L.; Bosmans, H.; Marshall, N. W.
Abstract : Purpose: : This work characterizes three candidate mammography phantoms with structured background in terms of power law analysis in the low frequency region of the power spectrum for 2D (planar) mammography and digital breast tomosynthesis (DBT). Methods: : The study was performed using three phantoms (spheres in water, Voxmam, and BR3D CIRS phantoms) on two DBT systems from two different vendors (Siemens Inspiration and Hologic Selenia Dimensions). Power spectra (PS) were calculated for planar projection, DBT projection, and reconstructed images and curve fitted in the low frequency region from 0.2 to 0.7 mm −1 with a power law function characterized by an exponent β and magnitude κ . The influence of acquisition dose and tube voltage on the power law parameters was first explored. Then power law parameters were calculated from images acquired with the same anode/filter combination and tube voltage for the three test objects, and compared with each other. Finally, PS curves for automatic exposure controlled acquisitions (anode/filter combination and tube voltages selected by the systems based on the breast equivalent thickness of the test objects) were compared against PS analysis performed on patient data (for Siemens 80 and for Hologic 48 mammograms and DBT series). Dosimetric aspects of the three test objects were also examined. Results: : The power law exponent ( β ) was found to be independent of acquisition dose for planar mammography but varied more for DBT projections of the sphere‐phantom. Systematic increase of tube voltage did not affect β but decreased κ, both in planar and DBT projection phantom images. Power spectra of the BR3D phantom were closer to those of the patients than these of the Voxmam phantom; the Voxmam phantom gave high values of κ compared to the other phantoms and the patient series. The magnitude of the PS curves of the BR3D phantom was within the patient range but β was lower than the average patient value. Finally, PS magnitude for the sphere‐phantom coincided with the patient curves for Siemens but was lower for the Hologic system. Close agreement of doses for all three phantoms with patient doses was found. Conclusions: : Power law parameters of the phantoms were close to those of the patients but no single phantom matched in terms of both magnitude ( κ ) and texture ( β ) for the x‐ray systems in this work. PS analysis of structured phantoms is feasible and this methodology can be used to suggest improvements in phantom design.